Diseño de la ampliación de la red de distribución de Gas Natural en el centro poblado San Antonio de Anapoima (2017)
In the present project of degree was realized the expansion of the natural gas distribution network of the Municipality of Anapoima, with the support of the Municipal Mayor's Office, from the use of technological tools such as Autocad and the Aspen Hysys Software. Based on the information obtained through a survey carried out on the inhabitants of San Antonio of Anapoima, the future demand for natural gas was determined, after which the design of the Gas Natural distribution network was carried out using the AutoCAD program and based on Colombian Technical Standard NTC 3728- Gas pipelines transportations and gas distribution, which specifies the parameters for the design, such as type of pipe, pipe diameters, materials, depths, pressures , temperatures, among others and the NTC 3838- Permissible operating pressures for the transportation, distribution and supply of combustible gases.